Nature’s Solvent Solution: Harnessing Natural Deep Eutectic Solvents (NADES) For Clean, Efficient Protein Isolation - Lee, Chi-Ching; Le, Thanh-Do; Pham, Bang Phuong; Tomas, Merve; Capanoglu, Esra; Ashaolu, Tolulope Joshua; Lee, Chı-Chıng (Springer, 2025)
Conventional protein extraction methods often face challenges such as low yields, long processing times, and environmen-tal concerns. Natural deep eutectic solvents (NADES), composed of natural hydrogen-bond donors and acceptors, offer a sustainable and efficient alternative. This review highlights traditional extraction techniques and their limitations then focuses on the advantages of NADES and explores the key factors that affect protein solubility and extraction efficiency. Various NADES components are evaluated for their roles in enhancing protein yield. NADES-extracted proteins exhibit high techno-functional properties beneficial for food systems. Life cycle analyses indicate carbon footprint reductions of 60–75% and energy savings of 40–65% relative to traditional extraction modes, while toxicological studies suggest that food-grade NADES formulations are safe. Recent advancements in applying NADES for protein recovery from oilseeds, legumes, and food by-products are also discussed. Despite their potential, issues like high viscosity and challenges in protein recovery and scalability remain. Current applications include sustainable food protein production, nutraceutical component manufacturing, and therapeutic pharmaceutical protein isolation, together with new opportunities with cellular agriculture and alternative protein technology. Future applications of work involve the computational-guided design of the NADES system, utilizing a Conductor-like Screening Model for Real Solvents (COSMO-RS) modeling to optimize continuous processing and to gain regulatory approval for applications in food-grade use. NADES technology embodies an important shift towards environ-mentally sustainable protein isolation that maximizes product quality, minimizes environmental impact, and is economically viable for multiple industries. The review concludes by outlining future research needs to improve NADES applications for green, high-performance protein extraction.
Keywords: Natural deep eutectic solvents; Food protein · Extraction; Sustainable solvents; Green chemistry